Abundance : the future is better than you think - Diamandis, Peter H.; Kotler, Steven, 1967- (New York : Free Press, 2012)
The authors document how four forces--exponential technologies, the DIY innovator, the Technophilanthropist, and the Rising Billion--are conspiring to solve our biggest problems. "Abundance" establishes hard targets for change and lays out a strategic roadmap for governments, industry and entrepreneurs, giving us plenty of reason for optimism.
Pt. 1: Perspective. Our grandest challenge -- Building the pyramid -- Seeing the forest through the trees -- It's not as bad as you think -- pt. 2: Exponential technologies. Ray Kurzweil and the go-fast button -- The singularity is nearer -- pt. 3: Building the base of the pyramid. The tools of cooperation -- Water -- Feeding nine billion -- pt. 4: The forces of abundance. The DIY innovator -- The technophilanthropists -- The rising billion -- pt. 5: Peak of the pyramid. Energy -- Education -- Health care -- Freedom -- pt. 6: Steering faster. Driving innovation and breakthroughs -- Risk and failure -- Which way next?
Includes bibliographical references (p. [305]-356) and index.
Keywords: Technological innovations -- Forecasting; Technological forecasting; Technology -- Social aspects; Social prediction; Economic forecasting